Pengaruh Terapi Infrared dan William Flexion Exercises terhadap Nyeri Punggung Bawah pada Petani Padi Lansia - Uswatun Hasanah; Fiqi Widyawati; Azizah Rahmawati; Young Ari Kusworo (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Elderly female rice farmers are vulnerable to chronic low back pain (LBP) due to prolonged bending activities, repetitive movements, and physical degeneration. This study analyzed the effects and the comparative effectiveness of infrared (IR) therapy and William Flexion Exercises (WFE) in reducing low back pain among elderly rice farmers. This study used a quasi-experimental design with a pre-test post-test control group design. The sample consisted of 30 elderly female rice farmers in Wukirsawit Village, Karanganyar (selected via purposive sampling), who were divided into the IR Group (n=15) and the WFE Group (n=15) for 12 sessions over 4 weeks. The measuring instrument used was the Visual Analog Scale (VAS), and the data were tested using the Wilcoxon Signed Rank Test and the Mann-Whitney U Test. Both interventions were proven to significantly reduce pain intensity (p<0.001). However, the between-group test showed a significant difference (p = 0.027), with the WFE group demonstrating a higher pain reduction effectiveness compared to IR therapy. These findings indicate that WFE can be prioritized as a primary active intervention for elderly rice farmers with LBP, while IR therapy can be used as a complementary modality prior to exercise.